Overview of Witloof Chicory (Cichorium intybus L.) Discolorations and Their Underlying Physiological and Biochemical Causes - De Jaegere, Isabel; Cornelis, Yannah; De Clerq, Tim; Goossens, Alain; Van De Poel, Bram (Frontiers in Plant Science, 2022)
Many fruits and vegetables suffer from unwanted discolorations that reduce product quality, leading to substantial losses along the supply chain. Witloof chicory (Cichorium intybus L. var. foliosum), a specialty crop characterized by its unique bitter taste and crunchiness, is particularly sensitive to various types of red and brown discolorations. The etiolated vegetable suffers from three predominant color disorders, i.e. core browning, internal leaf reddening and leaf edge browning. Additionally, several less frequently observed color disorders such as hollow pith, external red and point noir can also negatively affect crop quality. In this article, we bring together fragmented literature and present a comprehensive overview of the different discoloration types in chicory, and discuss their potential underlying physiological causes, including laticifer rupture, calcium deficiency and a disturbed water distribution. We also describe the role of environmental cues that influence discoloration incidence, including cultivation and postharvest storage conditions such as forcing and storage temperature, root ripeness and the duration of the forcing process. Finally, we zoom in on the underlying biochemical pathways that govern color disorders in witloof chicory, with a strong emphasis on polyphenol oxidase.